SMEs Sustainability in the Case of Japan: Localism or localization? - Tomoko Oikawa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
In this world we live in with urgent problems, climate crisis, in particular, localism and/or localization can be one answer to divert from global capitalism towards an alternative form of organization. SMEs account for around 99.7 % of the total number of enterprises, and 70% of total employment, in Japan. This figure is similar elsewhere in the world. It shows their economic and social importance at the local, regional and national levels. In fact, SMEs are rooted in the local society in terms not only of the economy but also tradition, culture and history. Thus, their sustainability correlates with local sustainability and regeneration. And, it is the local resources and environmental protection that both rely on along with agriculture, forestry, and fishery. It would be the focal point to look into the correlation between SMEs and the local economy possibly for localization. This paper focuses on SME under such circumstances concerning how they would regenerate their economic sustainability and be challenging self-sufficiency in association with the locals. For this, the paper argues how they cooperate and/or collaborate with the local institutions, government, and other enterprises, creating a type of associational economy. Regarding such issues, several case studies in Japan are provided. In looking these case studies through their managerial and organizational direction, it is indicated that they are giving a concrete form of “so-called” localization. In actuality, localism and/or localization are rather strange terms in Japan. Therefore, localism and localization are examined from the viewpoint how these ideas correspond with the regeneration of local economy. The literature review showed: (1) Localism is a social movement distinctive from localization. (2) Localization is a theory that would be realized through the associational economy and attained its vision of resolving the climate crisis. (3) Localism could indicate localization, but not necessarily. (4) It is found that membership philosophy is the base for this economy in Japan, while a similar kind of philosophy may be found or created for elsewhere.